TATA KELOLA HUMAS PEMERINTAH DAERAH, KAJIAN DI TIGA INSTANSI DI SUMATERA BARAT - M.A Dalmenda; Emeraldy Chatra (Jurnal Ranah Komunikasi, 2017)
In order for Government Public Relations to achieve its objectives as a bridge between government and society, good governance is needed. For this reason, the Indonesian Ministry of Administrative Reform and Bureaucratic Reform (Kemenpan) issued Permenpan No. 30/2011 concerning General Guidelines for Public Relations Governance in Government Agencies. After more than five years the Permenpan was issued, it was necessary to conduct research to monitor the extent to which improvements have been made to Government Public Relations. Monitoring in the form of research is considered important to know the diversity of government public relations governance practices. The study was conducted in three cities in West Sumatra, namely Padang, Solok and Payakumbuh. Research subjects are Government Public Relations officials, media practitioners, political activists and other relevant stakeholders. The research resulted in the finding that Permenpan No. 30/2011 has not become a reference for the work of the third Public Relations Division of the Municipal Government that was studied. The emphasis of public relations work is more on relations with the media (media relations) by prioritizing the publication of the activities of the mayor and deputy mayor. Attention to ten other types of publicity emphasized in Permenpan No. 30/2011 is minimal.